Electrocardiographic findings in a patient with pure septal infarction. Issue 3 (March 1991) - Tamura, A; Kataoka, H; Mikuriya, Y
Abstract : The electrocardiogram in a 65 year old man in whom pure septal infarction had been produced by occlusion of the septal branch during percutaneous transluminal coronary angioplasty showed that this had led to the disappearance of septal Q waves and reciprocal ST segment depression in the inferior leads.